Hubungan Diabetes Melitus (DM) dengan Penyakit Jantung Koroner (PJK) pada Pasien yang Berobat di Poli Jantung: Ida Rahmawati - Ida Rahmawati; Dian Dwiana; Rafidaini Sazarni Ratiyun (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Heart disease is a major health problem that can cause the highest death. The main factor of heart disease, one of which is uncontrolled blood sugar. The aim of this study is to determine relationship of diabetes mellitus with Coronary Heart Desease on Patients who treated at Heart Poly Dr. M. Yunus Hospital Bengkulu. Cross Sectional design used for this study and secondary data. Population in this study were all patients with Coronary Heart Disease who treated at Heart Poly dr. M. Yunus Hospital Bengkulu, there were 292 people. Sampling technique in this study used Total Sampling . collecting data in this study used documentation to obtained data about diabetes mellitus and coronary heart disease. Analyzed using univariate and bivariate. The results of this study showed: from 292 people, there were 183 people (62,7%) patients experienced chronic coronary heart disease and 109 (37,3%) patients experienced acute coronary heart disease, there were 173 people (59,2%) patients experienced diabetes melitus and 119 people (40,8%) patients did not experienced diabetes mellitus, there is significant relationship between diabetes mellitus with coronary heart disease on patients who treated at Heart Poly dr. M. Yunus Hospital Bengkulu, with closed category relationship. Patients who experienced diabetes mellitus have risk 16,996 times patients experienced coronary heart disease compared with patients who did not patients experienced diabetes mellitus. It is expected that people with diabetes mellitus can pay attention to dietary patterns and control blood sugar in order to be able to prevent coronary heart disease.